Microfluidic Techniques for Analytes Concentration - Zhao, Cunlu (2017)
Microfluidics has been undergoing fast development in the past two decades due to its promising applications in biotechnology, medicine, and chemistry. Towards these applications, enhancing concentration sensitivity and detection resolution are indispensable to meet the detection limits because of the dilute sample concentrations, ultra-small sample volumes and short detection lengths in microfluidic devices. A variety of microfluidic techniques for concentrating analytes have been developed. This article presents an overview of analyte concentration techniques in microfluidics. We focus on discussing the physical mechanism of each concentration technique with its representative advancements and applications. Finally, the article is concluded by highlighting and discussing advantages and disadvantages of the reviewed techniques.